La práctica inadecuada del inventario al patrimonio cultural, en el cantón San Miguel de Bolívar vulnera derechos a la propiedad privada, durante el año 2012 - Gaibor Monar., Silvana Estefania (2013)
To do a review on what they are and have been the processes of inventory to the knowledge of the cultural heritage of a nation is a difficult task for the aspects that it involves. However, in the light of the circumstances, has touched analyze a series of documents results of the work of registration of cultural heritage. Currently, the majority of the countries, before the need to know, appreciate and preserve the remnants of the past that make up the Cultural Heritage have established a endless regulations, agreements and other regulations that encourage and, in many cases they are forced, the realization of inventory projects which work in favor of the knowledge of the heritage with that account each locality. In the Canton of San Miguel the cases of destruction, lack of care, maintenance and dissemination we cannot fail to mention. How do you understand, for example, That lack of awareness by cultural heritage is destroyed once, the old water plant, the Centennial Park, which are public goods destroyed by neglect of the competent authorities, let alone the different homes with more than 100 years of construction in the urban area of the Canton, which their owners motivated to improve your lifestyle, health and hygiene, Since their properties are not in its most suitable to dwell in those places, the problems caused by inadequate management with regard to the protection, preservation, maintenance and dissemination of the cultural property and the observance of the rights of private property, on the part of the decentralized autonomous Government of the Canton of San Miguel's